Pertanggungjawaban Hukum Pengurus Perseroan Bank Jatim Atas Hapus Buku Kredit Yang Tidak Memenuhi Ketentuan - Rezky Wahyu Satrio; Widodo Widodo; Ibnu Subarkah (Pascasarjana Ilmu Hukum, Universitas Widyagama Malang, 2022)
PT Bank Pembangunan Daerah Jawa Timur (Bank Jatim) has PT Surya Graha Semesta Business Group as core debtor whose subsidiary, PT Nugraha Adi Taruna, was granted a KMK Pola Keppres for Kedungkandang Bridge construction work in Malang City. Based on Badan Pemeriksaan Keuangan Republik Indonesia examination result, the loan write-off did not meet the provisions. This thesis aims to find out the legal responsibility of the company management who writes off the loan that did not meet the provisions and can or cannot be categorized as a corruption crime and how legal remedies can be taken by minority shareholders in order not to be harmed by the actions of the company management. This thesis is classified as a doctrinal legal research because the study is focused on the consistency of the legal regulations governing the provisions for loan writing-off at Bank Jatim. The results of the study found that the KMK Pola Keppres PT NAT untuk Pekerjaan Pembangunan Jembatan Kedungkandang Kota Malang write-off conducted by Bank Jatim Company Management that did not meet the provisions in the Bank Jatim Director Decree and violated Otoritas Jasa Keuangan Republik Indonesia Regulations so that can be legally responsible administratively. Bank Jatim Company Management who writes off the loan by not fulfilling the provisions cannot be categorized as a corruption crime because it doesn’t fulfill one of the elements of corruption crime. Due to Bank Jatim Company Management actions, minority shareholders can take legal action by filing ordinary lawsuits and derivative lawsuits.